Linum usitatissimum Delivery over Chitosan Nanobiopolymer: Enhanced Effects on Polycystic Ovary Syndrome Condition - Abolfazl Bayrami; Maryam Sojoudi; Shima Rahim Pouran; Aziz Habibi-Yangjeh; Sanaz Sojoudi (IET Nanobiotechnology)
Herein, chitosan nanoparticle (CHIT) was used as a safe and biocompatible matrix to carry flaxseed (Linum usitatissimum L.) extract (FSE). The number of main features and bio-interface properties of CHIT-FSE were determined by SEM, DLS, FTIR, XRD, TGA, and zeta potential analyses and compared to those of chitosan lacking FSE. A GC–MS analysis was also conducted to reveal the bioactive compounds of FSE. The active anchoring of the FSE phytomolecules over chitosan nanoparticles with enhanced thermal and structural stability was correspondingly verified. Subsequently, the influence of CHIT-FSE, CHIT-TPP, and FSE supplementation was assessed on hormonal and biochemical markers of polycystic ovary syndrome (PCOS) in female rats and compared with untreated and healthy control groups. After 16 days of treatment, CHIT-FSE represented the best performance for controlling the serum levels of the studied biochemical (lipid profile and blood glucose level) and hormonal (insulin, testosterone, luteinizing, and follicle-stimulating hormone) parameters. Considering the negligible therapeutic activity of CHIT-TPP, the enhanced activity of CHIT-FSE compared to only FSE was expounded based on the potent action of chitosan nanoparticles in enhanced stabilization, bioavailability, transport, and permeability of the therapeutically important phytomolecules. As per the results of this investigation, supporting medically important biomolecules over chitosan can enhance their therapeutic effectiveness in controlling PCOS.